Nursing diagnoses and interventions in COVID-19 patients in intensive care units in 2nd level of care hospitals Zone 1 of Ecuador 2022: Nursing diagnoses and interventions in COVID-19 patients in intensive care units in 2nd level of care hospitals Zone 1 of Ecuador 2022. (La U Investiga, 2023)
The nursing care process is a tool that allows, in an organized manner, the development of care plans with diagnoses and interventions focused on each patient. The objective of the research was to determine the main diagnoses and interventions identified by intensive care nurses in patients with COVID 19; it is a quantitative, descriptive, cross-sectional study, the population consisted of 240 nursing professionals who work or worked in the intensive care unit of 4 hospitals in Zone 1. The following information was used for data collection a 21-question questionnaire with a Likert scale designed according to the COVID 19 patient care protocol proposed by the Ministry of Public Health and the Ecuadorian Federation of Nurses. The information was processed using the SPSS system. The results show that 7 diagnoses were identified out of a total of 10 proposed by the MSP; in Domain 3: elimination and exchange 1 diagnosis; Domain 4: activity and rest 3 in Domain 9 coping/stress tolerance 1 and in Domain 11 safety and protection 2; in relation to the interventions carried out, they are closely related to the diagnoses, according to those established in the NANDA, NIC and NOC taxonomy. It is concluded that the nursing professionals do not yet apply the nursing process, limiting themselves in most cases to collaborative care, although they have the COVID patient care protocol.
Keywords: nursing diagnosis; interventions; covid